Imaging of a glioma using peripheral benzodiazepine receptor ligands. - Starosta-Rubinstein, S (1987)
Two types of benzodiazepine receptors have been demonstrated in mammalian tissues, one which is localized on neuronal elements in brain and the other, on glial cells and in peripheral tissues such as kidney. In vivo administration of 3H-labeled PK 11195 [1-(2-chlorophenyl-N-methyl-N-(1-methylpropyl)-3-isoquinoline carboxamide] or [3H]flunitrazepam with 5 mg of clonazepam per kg to rats with intracranial C6 gliomas resulted in high levels of tritiated-drug binding to the tumor as shown by quantitative autoradiography. Pharmacological studies indicated that the bound drugs labeled the peripheral benzodiazepine binding site. Binding to the peripheral benzodiazepine site was confirmed primarily to malignant cells with little binding to adjacent normal brain tissue or to necrotic tissue. Tumor cell binding was completely inhibited by preadministration of the peripheral benzodiazepine blocking agent PK 11195 at 5 mg/kg. The centrally selective benzodiazepine ligand clonazepam had no effect on PK 11195 binding to the tumor cells. When binding to other tumor cell lines grown in nude mice and nude athymic rats was evaluated, little or no peripheral benzodiazepine binding was detected on human pheochromocytoma (RN1) and neuroblastoma (SK-N-MC, SK-N-SH) tumor cells, respectively. However, high densities of peripheral benzodiazepine binding sites were observed on tumors derived from a human glioma cell line (ATCC HTB 14, U-87 MG). The presence of high concentrations of specific peripheral benzodiazepine receptors on glial tumors suggests that human primary central nervous system tumors could be imaged and diagnosed using peripheral benzodiazepine ligands labeled with positron- or gamma-emitting isotopes.